Methylglyoxals, Thiocyanate, and Hydrogen Peroxide in saliva of newborns at risk of sepsis: Methylglyoxals as a promising biomarker of early-onset neonatal sepsis - Ari Yunanto; Pricilia Gunawan H; Eko Suhartono (Indonesian Journal of Perinatology, 2021)
Introduction. Sepsis represents a severe problem for newborns. The relatively high incidence rate of 1 to 10 cases per 1000 live births, with even higher rates in low-birth-weight neonates. Given its high incidence, identifying markers to optimize the early diagnosis and therapeutic interventions is highly desirable. This study investigates three oxidative markers taken from saliva, methylglyoxal (MG), Thiocyanate (SCN-) and hydrogen peroxide (H2O2), as early-onset neonatal sepsis markers. Methods. This study was conducted from June to August 2014, and saliva specimens were taken from 30 newborns of mothers with one major risk factor or two minor risk factors (case group) and 30 healthy newborns for the control group. Saliva levels of MG were determined by calculating the percentage of MG absorbance compared with the carbonyl compounds. Data were analyzed by using Kolmogorov-Smirnov and Student's t test. Results. We found a significant increase of SCN-, and MG level case group (28.91 mmol and 0.01%, respectively) compared to the control group (19.49 mmol and 0.005%, respectively) p-value = 0.03. In contrast, the H2O2 in the case group (32.56 mmol) was lower than the control group (37.47 mmol), with a p-value = 0.04. Conclusion. We found the increased levels of SCN–, MG and the decreased levels of H2O2 in neonates' saliva with the risk of sepsis. MG measurements as a routine diagnostic for suspected sepsis should be taken into consideration.